419 High-sensitivity troponins for outcome prediction in the general population: a systematic review and meta-analysis. (8th December 2021) - Aimo, Alberto; Georgiopoulos, Georgios; Panichella, Giorgia; Vergaro, Giuseppe; Passino, Claudio; Emdin, Michele; Clerico, Aldo
Abstract: Aims: High-sensitivity (hs) assays allow to measure cardiac troponin T and I (cTnT/I) even in healthy individuals. The higher hs-cTn values, the higher the ongoing cardiomyocyte damage, and then reasonably the risk of developing symptomatic cardiac disease. Methods and results: We retrieved all studies evaluating the prognostic value of hs-cTnT or I in the general population. We calculated pooled hazard ratio (HR) values for all-cause and cardiovascular death, cardiovascular events and heart failure (HF) hospitalization. We included 24 studies for a total of 203 202 subjects; 11 studies assessed hs-cTnT and 14 hs-cTnI. One standard deviation (SD) increase in baseline hs-cTn was associated with a 23% higher risk of all-cause death (HR: 1.226, 95% CI: 1.083–1.388, P < 0.001, I 2 = 88.5%); all these studies dosed hs-cTnI. In an exploratory analysis on three studies with 25 760 subjects, hs-cTn predicted cardiovascular death (HR: 1.822, 95% CI: 1.241–2.674, P = 0.002, I 2 = 87.2%). After synthesizing nine studies with 58 565 subjects, hs-cTn predicted cardiovascular events (HR: 1.328, 95% CI: 1.167–1.513, P < 0.001, I 2 = 93.8%). Both hs-cTnT (HR: 1.627, 95% CI: 1.145–2.311, P < 0.001) and hs-cTnI (HR: 1.260, 95% CI: 1.115–1.423, P < 0.001; p for interaction <0.001). Furthermore, in 10 studies with 61 467 subjects, hs-cTn predicted HF hospitalization (HR: 1.493, 95% CI: 1.368–1.630, P < 0.001, I 2 = 76.6%). Both hs-cTnT (HR: 1.566, 95% CI: 1.303–1.883, P < 0.001) and hs-cTnI (HR: 1.467, 95% CI: 1.321–1.628, P < 0.001) were associated with HF ho ( p for interaction <0.001). Conclusions: hs-cTn values hold strong prognostic value in subjects from the general population, predicting the risk of all-cause and cardiovascular mortality, cardiovascular events, and HF hospitalization.